Individual Test Rig for Measuring the Creep Behaviour of Corrugated Board for Packaging - Köstner, V.; Ressel, JB.; Sadlowsky, B.; Böröcz, P. (Acta Technica Jaurinensis, 2017)
Corrugated board is one of the most important and most popular packaging materials worldwide for transporting goods. Due to its hygroscopic behavior, it has a tendency to creep when subjected to stress under a constant load, which can ultimately result in loss of strength, with possible damage to products. The creep behavior of corrugated board is still a largely under-researched area. This paper attempts to examine the long-term behavior of corrugated board during use more precisely than before, and presents the first step and results of the research process. For the measurement, a compact and high-precision individual test rig was developed and used, in order to reduce the side effect of coupled systems, that is, to avoid their mutual influence. This paper successfully presents results reproducible with the described test rig apparatus for determining the creep behavior of corrugated board. It will be continued to publish further results of the research in the near future.